Financially-legal aspects of decentralization prosses of public administration in Ukraine today - Устинова, Ірина Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The objective of the article is the accumulation and review of existing regulatory material regarding the decentralization process, namely the implementation of fiscal decentralization, and financial and legal analysis of the current state of local Finance and their legal regulation reform in modern conditions of development of Ukraine taking into account foreign experience. The relevance of the research topics is the need of the modern understanding of legal regulation of decentralization processes in public administration of Ukraine and the state of development of law in these processes. Doclet themes. The problem of decentralization of financial resources and authority devoted a lot of research scientists (N. Bykadorova, A. Bondarenko, N. Kaminska, I. Karchevsky, P. Kolody, B. Krajnik, I. Legkostup, J. Ostroshenko and others) both in Ukraine and abroad. The author explores the concept of decentralization, financial decentralization, the decentralization of power. Analyzed the legal value of laws of Ukraine: "On principles of state regional policy" and "On voluntary consolidation of territorial communities" for further reform actions in Ukraine. Analyzed components of the new system in the formation of profitable and account parts of local budgets, the determination of the principles of transfer policy and intergovernmental relations. The main objectives of such a system and ways of their implementation are as follows: 1. Ensure fiscal autonomy and financial independence of local budgets 2. The consolidation of local budgets in the stable sources of income and stimulate podatkovni communities. 3. Strengthening the responsibility of relevant ministries for the balance of financial resources and sectoral policies, in particular through the mechanism of providing educational and medical subsidies, subsidies for personnel training. 4. The expansion of spending powers of local authorities by transferring funding from the local budgets of individual budget programmes and agencies, which are now financed from the state budget. 5. The introduction of a new mechanism of budgetary regulation and equalization. In Ukraine the process of fiscal decentralization takes place quite actively, consistently, with a fairly full legislative regulatory the development of this process, which is a positive thing for Ukraine in the historical development of both areas and the state.